AB0252 Benefit of Sarilumab with csDMARDs on Patient Productivity in Work, Household Work and Family, Social, Leisure Activities in TNF-IR RA Patients. (15th July 2016) - Strand, V.; Mahajan, P.; Chen, C.; van Hoogstraten, H.; Mangan, E.K.; Hagino, O.; Graham, N.; Pinheiro, G.da R.C.; Kivitz, A.
Abstract : Background: The effect of active rheumatoid arthritis (RA) on participation, active and meaningful engagement by patients in activities important to them, has significant individual and societal costs. Sarilumab is an investigational human anti–interleukin 6 (IL-6) receptor monoclonal antibody. In the phase 3 TARGET study (NCT01709578 ), sarilumab + conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) demonstrated efficacy in adults with moderate-to-severe, active RA and inadequate response to TNF inhibitors. The most common treatment-emergent adverse events were infections, neutropenia, and increased transaminases; laboratory changes were consistent with IL-6 signaling blockade. Objectives: To evaluate the effect of sarilumab treatment on patient productivity within and outside of the home; requirement for outside help; and family, social, or leisure activities in the past month as assessed by the RA-specific Work Productivity Survey (WPS-RA). 1 Methods: The intent-to-treat population included 546 patients randomized 1:1:1 to placebo, sarilumab 150 mg, or sarilumab 200 mg every 2 wks (q2w) subcutaneously (SC) + background csDMARDs. The WPS-RA was assessed for patients employed outside of (completed all 8 items) and within the home (completed only the 5 items related to productivity within the home and participation in family, social, and leisure activities) at baseline and wks 4 (not reported), 12, and 24. Mixed-model repeated measures analyses were used to evaluate differences in individual WPS-RA items at a significance level of 0.05 if O'Brien's global test 2 showed significance ( P <0.025). Results: At baseline, 544 patients were administered the WPS-RA, 33.1%, 33.7%, and 35.7% (placebo, sarilumab 150, and sarilumab 200 mg q2w SC, respectively) of whom were currently employed outside of the home. Global testing indicated significantly greater overall improvement in patients treated with sarilumab 150 mg q2w SC (wk 12, P =0.0010; wk 24, P =0.0004) and sarilumab 200 mg q2w SC (wk 12, P =0.0036; wk 24, P =0.0003) vs placebo. At wk 24, patients currently employed outside of the home receiving sarilumab 200 mg q2w SC reported significantly greater reductions in number of work days missed due to RA and less interference with work productivity. Patients receiving both doses reported significantly greater reductions in number of days missed engaging in household work, days requiring hired help, and rate of arthritis interference in household work and less time missed engaging in family, social, and leisure activities. Conclusions: Sarilumab treatment was associated with significant improvements in participation in work; household work; and family, social, and leisure activities. Improvements in productivity outside of the home were also significant among patients in the sarilumab 200 mg q2w SC group vs placebo, although only a proportion of patients worked outside of the home. These data indicate important improvements in overall participation following sarilumab treatment. References: Osterhaus et al. Arthritis Res Ther. 2009;11:R73 Tandon. Stat Med. 1990;9:819–827 Acknowledgement: This study was sponsored by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: V. Strand Consultant for: has received consulting fees from AbbVie, Amgen, AstraZeneca, Biogen, BMS, Celgene, Celltrion, Consortium of Rheumatology Researchers of North America (CORRONA), Crescendo/Myriad Genetics, EMD Serono, Genentech/Roche, GSK, Janssen, Eli Lilly, Novartis, Pfizer Inc, Regeneron Pharmaceuticals, Inc, Sandoz, Sanofi, and UCB., P. Mahajan Shareholder of: Sanofi, Employee of: Sanofi, C. Chen Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, H. van Hoogstraten Shareholder of: Sanofi, Employee of: Sanofi, E. Mangan Shareholder of: an employee of Regeneron Pharmaceuticals, Inc, and may hold stock and/or stock options in Pfizer Inc and Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc, O. Hagino Shareholder of: Sanofi, Employee of: Sanofi, N. Graham Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, G. da R.C. Pinheiro Consultant for: has received consulting fees from AbbVie, AstraZeneca, GSK, Hospira, Janssen, Pfizer Inc, Roche, RuiYi, and Sanofi., A. Kivitz Consultant for: has received consulting fees from Celgene, Genentech/Roche, GSK, Janssen, Pfizer Inc, Regeneron Pharmaceuticals, Inc, Sanofi, and UCB.